Integration of Computational Elements in the Development of Teaching Materials to Enhance Reading Comprehension Skills of Elementary School Students: A Systematic Literature Review - Ashari, Slamet; Citra Fitri Kholidya; Nurul Istiq’faroh (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
This study aims to examine the integration of computational thinking (CT) in developing teaching materials to enhance elementary students’ reading comprehension. Using a systematic literature review guided by PRISMA, 24 peer-reviewed articles published between 2020 and 2025 were analyzed, focusing on CT integration in reading instruction, the development of digital teaching materials and worksheets, and empirical evidence of effectiveness. The findings indicate that CT significantly improves reading comprehension through approaches such as story mapping, digital storytelling, gamification, and interactive worksheets, which support students in organizing ideas, identifying patterns, and constructing meaning from texts. The effectiveness is greater when CT is combined with narrative-centered learning, problem-based learning, and metacognitive strategies, as these approaches foster deeper engagement and critical thinking during the reading process. Additionally, CT-based interventions encourage active learning and promote students’ ability to interpret narrative texts more systematically. However, several limitations were identified, including small sample sizes, limited focus on interpretive comprehension, and context-specific implementations that may restrict generalizability. In conclusion, CT integration shows strong potential to improve elementary reading comprehension, but further comprehensive research is needed to explore long-term impacts, cross-cultural applicability, and the explicit integration of CT principles in literacy instruction, along with the development of standardized frameworks and teacher training programs to support effective and sustainable implementation.